Encyclopedia of world biography. Volume 35 Supplement. - Gale Group (Farmington Hills, Mich. Gale, Cengage Learning, 2015)
A multicultural biographical source that covers notable individuals from every part of the world and from all time periods who have made significant contributions to human culture.
Introduction -- Advisory board -- Obituaries -- Text -- How to use the index -- Index.
"ISSN 1099-7326".
Includes bibliographical references and index.
Keywords: Biography -- Encyclopedias; World history; Celebrities -- Biography; Statesmen -- Biography; Scholars -- Biography